Advances in Medical Revascularisation Treatments in Acute Ischemic Stroke. (30th December 2014) - Asadi, H.; Yan, B.; Dowling, R.; Wong, S.; Mitchell, P.
Abstract : Urgent reperfusion of the ischaemic brain is the aim of stroke treatment and there has been ongoing research to find a drug that can promote vessel recanalisation more completely and with less side effects. In this review article, the major studies which have validated the use and safety of tPA are discussed. The safety and efficacy of other thrombolytic and anticoagulative agents such as tenecteplase, desmoteplase, ancrod, tirofiban, abciximab, eptifibatide, and argatroban are also reviewed. Tenecteplase and desmoteplase are both plasminogen activators with higher fibrin affinity and longer half-life compared to alteplase. They have shown greater reperfusion rates and improved functional outcomes in preliminary studies. Argatroban is a direct thrombin inhibitor used as an adjunct to intravenous tPA and showed higher rates of complete recanalisation in the ARTTS study with further studies which are now ongoing. Adjuvant thrombolysis techniques using transcranial ultrasound are also being investigated and have shown higher rates of complete recanalisation, for example, in the CLOTBUST study. Overall, development in medical therapies for stroke is important due to the ease of administration compared to endovascular treatments, and the new treatments such as tenecteplase, desmoteplase, and adjuvant sonothrombolysis are showing promising results and await further large-scale clinical trials.